Neuronal Morphology and Synapse Count in the Nematode Worm - Friedman, Robert (Frontiers in Computational Neuroscience, 2019)
The somatic nervous system of the nematode worm Caenorhabditis elegans is a model for understanding the physical characteristics of the neurons and their interconnections. Its neurons show high variation in morphological attributes. This study investigates the relationship of neuronal morphology to the number of synapses per neuron. Morphology is also examined for any detectable association with neuron cell type or ganglion membership.